Systematic Review: The Relationship of Spouses’ Support and Postpartum Depression - Sinta Effelia Agatra; Ira Titisari; Indah Rahmaningtyas; Finta Isti Kundarti (Journal of Ners and Midwifery, 2023)
Postpartum depression is a mental health problem experienced by mothers at 4 weeks after giving birth which is characterized by feelings of sadness, decreased mood, feelings of failure or guilt, and even suicidal ideation, one of which is due to lack of husband support. To analyze the incidence of postpartum depression, the provision of husband support, and the relationship between providing husband support to the incidence of postpartum depression. This study used a systematic review design by tracing journal articles through the database like as Proquest, Garuda Portal, PubMed, and Science Direct with the publication year from January 2012 - January 2022 and discussing husband support and the incidence of postpartum depression, and using Indonesian and English. The keywords used in national journal were "husband's support" and "postpartum depression" or "postpartum depression", for international journal articles used "spousal support" or "partner support" or "husband's support" and "postpartum depression. The results showed that 10 journal articles met the inclusion criteria with all journal articles stating that there was a relationship between husband support and the incidence of postpartum depression. Most postpartum mothers do not experience postpartum depression and receive husband's support. There was a relationship between providing husband's support and the incidence of postpartum depression, where the higher the husband's support, the lower postpartum depression that occurs in postpartum mothers. The results of the study found 10 journal articles that met the inclusion criteria with all journal articles stating that there was a relationship between the provision of husband support and the incidence of postpartum depression.